The Culture of Nepotism in Bureaucratic Recruitment Through Legal Sociology Analysis - Arief Fahmi Lubis; Latifa Dinar Rahmani Hakim; Reza Firmansyah; Ahmad Taufiq (Mahkota Science Publishers, 2026)
The practice of nepotism persists as a social phenomenon that reflects the fundamental tension between the impersonal logic of state law and the structures of family solidarity and patronage networks that remain deeply rooted in Indonesian social culture. This study aims to provide a comprehensive analysis of how a culture of nepotism is formed and maintained within the bureaucratic recruitment process in Indonesia, through the lens of legal sociology. This study employs a qualitative, socio-legal research design focused on legal-sociological analysis to gain a deep understanding of how the culture of nepotism is formed, reproduced, and legitimised in bureaucratic recruitment practices in Indonesia. The findings confirm that the problem of nepotism lies not only in the weak enforcement of rules, but in the mismatch between the design of state institutions and the collectivist cultural structure of society. Consequently, efforts at bureaucratic reform that rely solely on anti-nepotism regulations are likely to fail unless accompanied by a transformation of power relations and a more equitable distribution of social access. Therefore, a shift in perspective is required: from a moralistic approach that merely condemns nepotism towards a structural approach that seeks to understand and redesign bureaucratic institutions so that they can bridge the demands of meritocracy with the social realities of society.